MAIN DIRECTIONS OF ACCELERATING REGIONAL SOCIO-ECONOMIC DEVELOPMENT IN THE DIGITAL ERA - Aliyeva Tofik Ruhangiz; Aliyev Zaur Farid (Agora International Journal of Economical Sciences (AIJES), 2023)
International experiences show that one of the most important indicators for the sustainable and balanced development of each country is the socio-economic development level of the country's regions. The digital information presented by the digital economy is widely used in the direction of solving the socio-economic problems of the regions and opens great opportunities for increasing the effectiveness of the economic policy of the regions. Ensuring sustainable economic and social development of regions is part of the regional economic policy implemented by the state. Currently, in the international practice, the regional policy of the state is evaluated as an activity of managing economic and social development in the country through the creation of economic relations between the state and the regions of the country. Despite the implementation of a number of state programs in the field of socio-economic development of regions in the country, as well as the attention paid to regional development issues in a some program documents of the government and the achievement of certain progress in this direction, sharp differences and inequality between the levels of socio-economic development of the country's regions continue. does. This difference is particularly sharp between the Baku-Absheron zone and all other regions of the country. In the article, the current state of inequality in regional socio-economic development is analyzed based on official statistical data and its causes are investigated. Then, the policy steps implemented by the government so far in order to eliminate this problem are examined.The article examines the impact of measures resulting from the analysis of state programs and strategic road maps on the socio-economic development of regions. In the end, the economic benefits of digitization in economic regions were specified and presented in the form of recommendations.
Keywords: 330